A Case Report of Angiosarcoma of Maxillary Gingiva: Histopathology Aspects - Firstine Kelsi Hartanto; Shin Hin Lau (Faculty of Dentistry, Universitas Trisakti, 2018)
Background: Angiosarcoma is a rare malignant tumor, which most often occurs in the skin and soft tissue. Its occurrence in the head and neck region, and the intraoral region in particular, is uncommon. The aim of this case report is to highlight the importance of histopathological examination and to underscore the characteristic features of angiosarcoma. Case report: A 52-year-old female presented with a growth in the right maxillary portion of the interdental region of her molar teeth. The growth had been present for approximately one month. A computerized tomography (CT) scan showed metastatic tumors in the lungs, liver, bone, and soft tissue of maxillary gingiva. Intraoral examination found a soft and mobile pedunculated ovoid mass at the right palatal gingiva; the mass was reddish-blue in color. An incisional biopsy was performed to confirm the diagnosis and plan for further treatment. Histopathologic examination revealed malignant endothelial cells in a vasoformative growth pattern, with numerous vascular channels lined with neoplastic endothelium-forming intraluminal buds, projections, and papillae. These projections were interspersed with the tumor cells. Immunohistochemistry analysis showed these endothelial cells demonstrated strong positive immunoreactivity with CD31, factor VIII, and FLi-1. A diagnosis of angiosarcoma was made. Discussion: Because intraoral angiosarcoma is rare and its clinical presentation can resemble other vascular lesions, it can be a challenging diagnosis for clinicians and pathologists. In the present case, the diagnosis of intraoral angiosarcoma was made based on clinical and histopathology findings. The microscopic features of malignant endothelial cells and the presence of intraluminal projections, supported by positive immunoreactivity with CD31, factor VIII, and FLi-1, confirmed the diagnosis. Conclusion: Angiosarcoma poses a diagnostic challenge to dental practitioners and oral pathologists due to the rarity of occurrence in the oral cavity. Histopathological examination is critical for an accurate diagnosis.